Comparative Microstructural Evaluation of Wood in Three Dominant Ziziphus Species of Desert Ecosystem (Cholistan), Pakistan - Muhammad Bilal; Zaheer-ud-din Khan; Sohaib Muhammad; Uzma Hanif; Khalid Hussain; Muhammad Tayyab; Andleeb Anwar Sardar; Hassan Nawaz; Muhammad Jawad Tariq Khan; null Mahrukh; Aneela Rasool; Summiya Faisal; et al. (Scientifica)
The present microstructural evaluation was carried out on the woods of three ethnobotanically important local fruit trees, namely, Ziziphus mauritiana Lam., Z. spina-christi (L.) Willd., and Z. nummularia (Burm.f.) Wight and Arn., of family Rhamnaceae from Cholistan Desert of Pakistan. Wood samples were sectioned with sliding sledge microtome to make permanent slides for observing different anatomical parameters under the light microscope. All selected species were observed to have diffuse-porous wood with indistinct growth rings. The vessels were rounded in outline in all the species studied and found mostly solitary or in radial multiples of 2 in Ziziphus mauritiana and Z. nummularia, while in radial multiples of 2 to 5 in Z. spina-christi. The intervessel pits were scalariform to opposite. The rays were uniseriate in Ziziphus mauritiana, while mostly were biseriate in Ziziphus spina-christi. Simple perforation plates and diffuse, confluent, and vasicentric types of axial parenchyma were present in all the selected species. The fibers were thin-walled and nonseptate. One-way ANOVA followed by the Tukey test was conducted to observe different anatomical variations within selected species. Principal component analysis revealed correlations among studied anatomical parameters. The number of rays per mm was comparatively larger in Ziziphus nummularia, showing its greater susceptibility to wood-deteriorating agents than in other selected species. The Runkel ratio indicated the selected species suitable for making paper.